A retrospective analysis of blood culture-negative endocarditis at a tertiary care centre in Switzerland (Swiss Medical Weekly, 2022)
AIMS OF THE STUDY: Numerous studies from different countries have contributed to an improved understanding of blood culture-negative infective endocarditis. However, little is known about its epidemiology and microbiology in Switzerland. We aimed to assess the epidemiology and microbiology of blood culture-negative endocarditis at the University Hospital Zurich, Switzerland. METHODS: We screened all patients hospitalised between 1997 and 2020 with possible or definite endocarditis at our institution. Thereof, we identified all cases with blood culture-negative endocarditis and retrospectively retrieved patient characteristics, microbiological, histopathological, radiographic and surgical data from medical records.RESULTS: Among 861 patients screened, 66 (7.7%) cases of blood culture-negative endocarditis were identified. Thereof, 31 cases could be microbiologically documented or not documented (n = 30), and in five cases a non-infectious aetiology was confirmed. Endocarditis predominantly affected men (77%) and the left heart (79%); predisposing factors were prosthetic valves (42%), congenital heart disease (35%) and prior endocarditis (14%). The most common reasons for negative blood cultures were antibiotic treatment prior to blood culture sampling (35%), fastidious and slow growing microorganisms (30%) and definite non-infective endocarditis (8%). Coxiella burneti i and Bartonella spp. were the most common fastidious bacteria identified. In addition to serology, identification of causative microorganisms was possible by microbiological and/or histopathological analysis of tissue samples, of which polymerase chain reaction testing (PCR) of the 16S ribosomal RNA proved to be most successful.CONCLUSIONS: The present study provides a detailed analysis of blood culture-negative endocarditis over a time span of more than 20 years in Zurich, Switzerland. Antibiotic treatment prior to blood collection, and fastidious and slow growing organisms were identified as main reasons for sterile blood cultures. Typical culture-negative bacteria were mainly found by PCR and/or culture of tissue samples.